Origins of the Bill of Rights - Levy, Leonard W. (Leonard Williams), 1923-2006 (Yale University Press, 1999)
In this history of the origins of the Bill of Rights, Pulitzer Prize-winning historian Leonard W. Levy offers a panoramic view of the liberties secured by the first ten amendments to the Constitution. Levy illuminates the behind-the-scenes maneuverings, public rhetoric, and political motivations of James Madison and others who overcame fierce opposition to ensure the ratification of these crucial liberties.
Keywords: United States. -- Constitution. -- 1st-10th Amendments -- History.; Constitution (United States); Civil rights -- United States -- History.; Droits de l'homme -- États-Unis -- Histoire.; LAW -- Constitutional.; LAW -- Public.; Civil rights; United States; Grondrechten.; Bill of Rights (Verenigde Staten); Verenigde Staten.; Droits de l'homme -- Etats-Unis -- Histoire.; Etats-Unis -- Histoire constitutionnelle.; Etats-Unis -- Constitution -- Amendements (01er-10e) -- Histoire.; History